APPLICATION OF THE GEOGEBRA PROGRAM FOR THE ORGANIZATION OF EDUCATIONAL AND COGNITIVE PUPIL'S ACTIVITIES - Khrushch, Lesya; Lototskyi, Vasyl (Mountain School of Ukrainian Carpaty, 2019)
The article summarizes the experience of using GeoGebra software tools as a system for activating educational and cognitive activity of pupils in the process of learning mathematics. An important task of school education is the presentation of logically structured material with some elements of graphical representation for quick perception and processing of the necessary information, therefore, of course, in the process of teaching mathematical disciplines it is expedient to use separate components of a computer-oriented learning system for the development of project and research activities of pupils. In this research work functional capabilities of the system of dynamic mathematics from the point of view of innovation and prospects of its use in the educational process are analyzed. The possibility of organizing an empirical study of the properties of mathematical objects is considered. Different groups of problems are created, solving which it is advisable to use the software for automation of constructions and computing GeoGebra. Some examples are given on application of dynamic mathematical modeling programs to different types of tasks and methodical peculiarities of using an interactive mathematical environment. It is analyzed that, in the process of learning mathematics, system GeoGebra is used as the mean for visualization of the studied mathematical objects, expressions, depicting methods of construction; as an environment for modeling and "mathematical experiment" to identify the properties of the objects under reseach; as an instrumental computing complex. The importance of implementation of solving research problems theory with the use of information and communication technologies is confirmed, this will promote a pupils’ interest in the process of learning, the development of pupils’research activities, increase their mental activity and will provide the student with a set of specialized tools for creating and transforming objects, as well as measuring the required parameters.